Methodological Aspects of Formation and Development of National Innovation Systems - TUREKULOVA, Dametken; MUKHAMBETOVA, Lyazzat; KURMANKULOVA, Nurzhamal; KEMALOVA, Ainur; SATKANOVA, Rimma; BERMUKHAMEDOVA, Galiya (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018, 2019)
The article considers various approaches to the understanding of the term "national innovation system", presents the author's vision of this category. The history of the emergence and evolution of the development of the concept of a national innovation system has been studied, the main directions for the development of national innovation systems in foreign countries, and tools to support the national innovation system are presented. The characteristic of models of national innovation systems is given.